Role of EDAPTMS-Functionalized Silica Derived from Rice Husk Ash in the Adsorption Kinetics of Cu(II), Cr(III), and Pb(II) - Is Fatimah; Tesha Yuliarni; Dian Riyanti (Bulletin of Chemical Reaction Engineering & Catalysis, 2018)
In the present work, synthesis of (3-ethylene diamino propyl)-trimethoxysilane (EDAPTMS)-functionalized silica prepared from rice husk ash (RHA) and its adsorptivity of Cu(II), Cr(III), and Pb(II) in an aqueous solution was investigated. The EDAPTMS-functionalized silica was prepared by destruction of RHA with 4 M NaOH solution followed by functionalization by using the sol-gel method. The interaction was engaged by mixing EDAPTMS with silica gel in an acid condition followed by aging. The gel obtained from the procedure was analyzed by using X-ray diffraction (XRD), infrared spectroscopy (FTIR), and a surface area analyzer (SAA). Effect of EDAPTMS content on the material character and adsorption capability are the focuses of the study. The adsorption study was conducted in a batch adsorption system for Cu(II), Cr(III), and Pb(II) mixed solution and metal ion analyses were performed by atomic absorption spectrophotometry. The results showed that enhancement of physicochemical character was obtained after modification Based on the quantitative analysis of each metal, the kinetics of adsorption of a single solution of each ion and mixed solutions were studied. as shown by the increasing specific surface area as well as the increasing adsorption rate of the metal ions along increasing EDAPTMS content. Langmuir and Freundlich models were utilized for the kinetic study. Adsorption selectivity and adsorption kinetics were found to be strongly influenced by ionic coordination bonding with metal ions. The interpretation of the kinetic models showed the fitness of the Freundlich model for all metal ions.